2020
DOI: 10.1038/s41467-020-16969-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic drug target validation using Mendelian randomisation

Abstract: Mendelian randomisation (MR) analysis is an important tool to elucidate the causal relevance of environmental and biological risk factors for disease. However, causal inference is undermined if genetic variants used to instrument a risk factor also influence alternative disease-pathways (horizontal pleiotropy). Here we report how the 'no horizontal pleiotropy assumption' is strengthened when proteins are the risk factors of interest. Proteins are typically the proximal effectors of biological processes encoded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
262
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 261 publications
(304 citation statements)
references
References 75 publications
6
262
0
Order By: Relevance
“…It is therefore not possible to perform the additional quality control discussed below, which illustrates that results based on one or two SNPs should be interpreted with caution. It is noteworthy that previous eQTL-based MR studies have reported heterogeneity between tissues, both in terms of the magnitude and direction of effect (Schmidt et al 2020) We consider the MR result more robust if several meta-analysis methods yield a similar result, such as the maximum likelihood and MR-Egger methods (Haycock et al 2016;Burgess et al 2019;Slob and Burgess 2020). This is only possible if > 2 SNPs are available per gene, and we found that all eight genes with > 2 SNPs reached at least nominal significance using the maximum likelihood method (unadjusted < 0.05).…”
Section: Mr Quality Control Suggests That Cd38 Gpnmb and Map3k12 Hamentioning
confidence: 92%
See 4 more Smart Citations
“…It is therefore not possible to perform the additional quality control discussed below, which illustrates that results based on one or two SNPs should be interpreted with caution. It is noteworthy that previous eQTL-based MR studies have reported heterogeneity between tissues, both in terms of the magnitude and direction of effect (Schmidt et al 2020) We consider the MR result more robust if several meta-analysis methods yield a similar result, such as the maximum likelihood and MR-Egger methods (Haycock et al 2016;Burgess et al 2019;Slob and Burgess 2020). This is only possible if > 2 SNPs are available per gene, and we found that all eight genes with > 2 SNPs reached at least nominal significance using the maximum likelihood method (unadjusted < 0.05).…”
Section: Mr Quality Control Suggests That Cd38 Gpnmb and Map3k12 Hamentioning
confidence: 92%
“…For example, an eQTL associated with reduced expression of HMGCR mimics exposure to an HMGCR-inhibitor, such as a statin. Most clinically-used drugs target proteins, and genetic variants associated with protein levels in a clinically relevant tissue may be ideal to model drug target effects with MR (Schmidt et al 2020). However, even with high throughput protein assays, the spectrum of reliable, wellpowered GWAS data on protein targets is limited.…”
Section: Mimicking Medications With Expression Quantitative Trait Locimentioning
confidence: 99%
See 3 more Smart Citations